2017
DOI: 10.1080/15361055.2017.1330641
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Fusion Materials Development Path to DEMO

Abstract: This paper reports Japanese strategy for developing blanket structural materials for DEMO. In the Japanese program, the candidate materials are categorized into Primary Option (RAFM) and Advanced Options (V-alloy, SiC/SiC, ODS-RAFM etc.). A staged development is planned corresponding to the three decision-making points (DPs), DP1 : Intermediate check and review (C&R), DP2 : Decision of transition of research and development (R&D) focus to DEMO, and DP3 : Decision of DEMO construction. The near-term D-Li neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Figure 2 shows the prediction of loss of elongation of RAFM by irradiation and strategy of testing [6]. From previous neutron irradiation experiments with fission test reactors, it is found that the total elongation of RAFM tends to be harden to around 10% and keeps the value of around 7%.…”
Section: Reduced Activation Ferritic-martensitic Irradiationmentioning
confidence: 99%
“…Figure 2 shows the prediction of loss of elongation of RAFM by irradiation and strategy of testing [6]. From previous neutron irradiation experiments with fission test reactors, it is found that the total elongation of RAFM tends to be harden to around 10% and keeps the value of around 7%.…”
Section: Reduced Activation Ferritic-martensitic Irradiationmentioning
confidence: 99%
“…To enable the construction and operation of DEMO, it is necessary to evaluate precisely the behavior of materials in DEMO environments. For this purpose, construction of a high-quality material irradiation database is thought to be essential [22]. However, irradiation data can contain various problems.…”
Section: Proposals Regarding the Future Direction Of Irradiation Rese...mentioning
confidence: 99%
“…The A-FNS generates the large number of neutrons with the broad energy peak of around 14 MeV as shown in figure 1. The ratio of the produced amounts of the helium in the iron to the amounts of the displaced atoms caused by the neutron irradiations is a factor of around 15 [17,[38][39][40][41][42]. Since it is almost the same value as that at the first wall of the Japanese fusion DEMO reactor, the irradiation tests by using A-FNS are very useful for validation of DEMO materials design.…”
Section: Introductionmentioning
confidence: 99%